2016
DOI: 10.5194/hess-2016-121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global-scale two-layer transient groundwater model: development and application to groundwater depletion

Abstract: Abstract. Groundwater is the world's largest accessible source of freshwater to satisfy human water needs. Moreover, groundwater buffers variable precipitation rates over time, thereby effectively sustaining river flows in times of droughts as well as evaporation in areas with shallow water tables. Lateral flows between basins can be a significant part of the basins water budget, but most global-scale hydrological models do not consider surface water-groundwater interactions and do not include a lateral ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 14 publications
2
71
0
Order By: Relevance
“…Studies in the past have suggested groundwater may not exert strong controls to the near‐surface soil dynamics when it is far from the surface (Maxwell & Kollet, 2008; Ferguson & Maxwell, 2010; Lo & Famiglietti, 2010). However, the use of JULES‐GFB even for deep aquifer systems may be justified if the purpose is to use JULES applied to water resources studies where a representative volume of subsurface water is a key component of the study (de Graaf et al, 2017; Fan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the past have suggested groundwater may not exert strong controls to the near‐surface soil dynamics when it is far from the surface (Maxwell & Kollet, 2008; Ferguson & Maxwell, 2010; Lo & Famiglietti, 2010). However, the use of JULES‐GFB even for deep aquifer systems may be justified if the purpose is to use JULES applied to water resources studies where a representative volume of subsurface water is a key component of the study (de Graaf et al, 2017; Fan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The aquifer hydrogeologic parameters in this model were determined from global‐scale lithology (Hartmann & Moosdorf, ), and transmissivities were derived using shallow bedrock permeability data from Gleeson et al (). Based on this single layer steady state model, De Graaf et al () further extended this model to a two‐layer transient model for both confined and unconfined aquifer systems. The transient model was developed by coupling the hydrological model PCR‐GLOBWB (Van Beek et al, ) and the groundwater model using MODFLOW (McDonald & Harbaugh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al () also developed an empirical‐based map of soil permeability that targets the shallow vadose zone (~1‐ to 2‐m depth) based on the U.S. soils map (http://ldas.gsfc.nasa.gov/) but does not include the permeability of bedrock. ( De Graaf et al, ) used both sedimentary and the shallow bedrock permeability data sets to represent the subsurface, including confining units, by developing geometric relationships between surficial expressions of units and their potential depth relationships. Recreating the hydrogeologic structure of the subsurface over large scales remains a major source of uncertainty in applying groundwater flow models accurately at continental scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge is to estimate spatial variations in the storage and transmission properties of the landscape. Advances are possible through the development of new data sources on geophysical attributes (Simard et al, 2011;Gleason and Smith, 2014;Fan et al, 2015;Chaney et al, 2016b;Pelletier et al, 2016;De Graaf et al, 2017), new approaches to link geophysical attributes to model parameters (Samaniego et al, 2010;Kumar et al, 2013;Rakovec et al, 2015), and new diagnostics to infer model parameters Yilmaz et al, 2008;Pokhrel et al, 2012). Such focus will give the parameter estimation problem the scientific attention that it deserves, rather than the far-too-common approach where parameter estimation is relegated to a "tuning exercise" in model applications.…”
Section: Summary and Next Stepsmentioning
confidence: 99%